Tracing heme in a living cell: hemoglobin degradation and heme traffic in digest cells of the cattle tick Boophilus microplus - Lara, F. A.; Lins, U.; Bechara, G. H.; Oliveira, P. L. (Company of Biologists Ltd, 2005)
Heme is present in all cells, acting as a cofactor in essential metabolic pathways such as respiration and photosynthesis. Moreover, both heme and its degradation products, CO, iron and biliverdin, have been ascribed important signaling roles. However, limited knowledge is available on the intracellular pathways involved in the flux of heme between different cell compartments. The cattle tick Boophilus microplus ingests 100 times its own mass in blood. The digest cells of the midgut endocytose blood components and huge amounts of heme are released during hemoglobin digestion. Most of this heme is detoxified by accumulation into a specialized organelle, the hemosome.We followed the fate of hemoglobin and albumin in primary cultures of digest cells by incubation with hemoglobin and albumin labeled with rhodamine. Uptake of hemoglobin by digest cells was inhibited by unlabeled globin, suggesting the presence of receptor-mediated endocytosis. After endocytosis, hemoglobin was observed inside large digestive vesicles. Albumin was exclusively associated with a population of small acidic vesicles, and an excess of unlabeled albumin did not inhibit its uptake. The intracellular pathway of the heme moiety of hemoglobin was specifically monitored using Palladium-mesoporphyrin IX (Pd-mP) as a fluorescent heme analog. When pulse and chase experiments were performed using digest cells incubated with Pd-mP bound to globin (Pd-mP-globin), strong yellow fluorescence was found in large digestive vesicles 4 h after the pulse. By 8 h, the emission of Pd-mP was red-shifted and more evident in the cytoplasm, and at 12 h most of the fluorescence was concentrated inside the hemosomes and had turned green. After 48 h, the Pd-mP signal was exclusively found in hemosomes. In methanol, Pd-mP showed maximal emission at 550 nm, exhibiting a red-shift to 665 nm when bound to proteins in vitro.The red emission in the cytosol and at the boundary of hemosomes suggests the presence of heme-binding proteins, probably involved in transport of heme to the hemosome. The existence of an intracellular heme shuttle from the digestive vesicle to the hemosome acting as a detoxification mechanism should be regarded as a major adaptation of ticks to a blood-feeding way of life. To our knowledge, this is the first direct observation of intracellular transport of heme in a living eukaryotic cell. A similar approach, using Pd-mP fluorescence, could be applied to study heme intracellular metabolism in other cell types.
Keywords: palladium mesoporphyrin; endocytosis; hematophagy; hemosome; Cattle tick; Boophilus microplus